Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To construct a quadratic equation given its roots, we need to use the fact that for a quadratic equation of the form [tex]\( ax^2 + bx + c = 0 \)[/tex], if [tex]\(\alpha\)[/tex] and [tex]\(\beta\)[/tex] are the roots, then:
1. The sum of the roots, [tex]\(\alpha + \beta = -\frac{b}{a}\)[/tex]
2. The product of the roots, [tex]\(\alpha \beta = \frac{c}{a}\)[/tex]
Given the roots [tex]\(\frac{4}{5}\)[/tex] and [tex]\(-2 \frac{2}{3}\)[/tex], we first convert these numbers to a common fraction form:
- [tex]\(\frac{4}{5}\)[/tex] is already in fraction form.
- [tex]\(-2 \frac{2}{3}\)[/tex] can be converted to an improper fraction:
[tex]\[ -2 \frac{2}{3} = -\left(2 + \frac{2}{3}\right) = -\left(\frac{6}{3} + \frac{2}{3}\right) = -\frac{8}{3} \][/tex]
Now, let's denote the roots as:
[tex]\[ \alpha = \frac{4}{5}, \quad \beta = -\frac{8}{3} \][/tex]
Step 1: Calculate the sum of the roots.
Sum of the roots [tex]\(\alpha + \beta\)[/tex] is:
[tex]\[ \alpha + \beta = \frac{4}{5} + \left( -\frac{8}{3} \right) \][/tex]
To add these fractions, we need a common denominator. The least common multiple of 5 and 3 is 15. Converting both fractions to have this common denominator:
[tex]\[ \frac{4}{5} = \frac{4 \times 3}{5 \times 3} = \frac{12}{15}, \quad -\frac{8}{3} = \frac{-8 \times 5}{3 \times 5} = \frac{-40}{15} \][/tex]
Now we can add them:
[tex]\[ \frac{12}{15} + \frac{-40}{15} = \frac{12 - 40}{15} = \frac{-28}{15} \][/tex]
Step 2: Calculate the product of the roots.
Product of the roots [tex]\(\alpha \beta\)[/tex] is:
[tex]\[ \alpha \beta = \left(\frac{4}{5}\right) \left(-\frac{8}{3}\right) \][/tex]
Multiplying the fractions:
[tex]\[ \left(\frac{4}{5}\right) \left(-\frac{8}{3}\right) = \frac{4 \times (-8)}{5 \times 3} = \frac{-32}{15} \][/tex]
Step 3: Write the quadratic equation using the sum and product of the roots.
In general, the quadratic equation based on the sum and product of the roots is given by:
[tex]\[ x^2 - (\text{sum of roots})x + (\text{product of roots}) = 0 \][/tex]
Plugging in our values:
[tex]\[ x^2 - \left(\frac{-28}{15}\right)x + \left(\frac{-32}{15}\right) = 0 \][/tex]
Simplifying the signs:
[tex]\[ x^2 + \frac{28}{15}x - \frac{32}{15} = 0 \][/tex]
Thus, the quadratic equation whose roots are [tex]\(\frac{4}{5}\)[/tex] and [tex]\(-2\frac{2}{3}\)[/tex] is:
[tex]\[ x^2 + \frac{28}{15}x - \frac{32}{15} = 0 \][/tex]
1. The sum of the roots, [tex]\(\alpha + \beta = -\frac{b}{a}\)[/tex]
2. The product of the roots, [tex]\(\alpha \beta = \frac{c}{a}\)[/tex]
Given the roots [tex]\(\frac{4}{5}\)[/tex] and [tex]\(-2 \frac{2}{3}\)[/tex], we first convert these numbers to a common fraction form:
- [tex]\(\frac{4}{5}\)[/tex] is already in fraction form.
- [tex]\(-2 \frac{2}{3}\)[/tex] can be converted to an improper fraction:
[tex]\[ -2 \frac{2}{3} = -\left(2 + \frac{2}{3}\right) = -\left(\frac{6}{3} + \frac{2}{3}\right) = -\frac{8}{3} \][/tex]
Now, let's denote the roots as:
[tex]\[ \alpha = \frac{4}{5}, \quad \beta = -\frac{8}{3} \][/tex]
Step 1: Calculate the sum of the roots.
Sum of the roots [tex]\(\alpha + \beta\)[/tex] is:
[tex]\[ \alpha + \beta = \frac{4}{5} + \left( -\frac{8}{3} \right) \][/tex]
To add these fractions, we need a common denominator. The least common multiple of 5 and 3 is 15. Converting both fractions to have this common denominator:
[tex]\[ \frac{4}{5} = \frac{4 \times 3}{5 \times 3} = \frac{12}{15}, \quad -\frac{8}{3} = \frac{-8 \times 5}{3 \times 5} = \frac{-40}{15} \][/tex]
Now we can add them:
[tex]\[ \frac{12}{15} + \frac{-40}{15} = \frac{12 - 40}{15} = \frac{-28}{15} \][/tex]
Step 2: Calculate the product of the roots.
Product of the roots [tex]\(\alpha \beta\)[/tex] is:
[tex]\[ \alpha \beta = \left(\frac{4}{5}\right) \left(-\frac{8}{3}\right) \][/tex]
Multiplying the fractions:
[tex]\[ \left(\frac{4}{5}\right) \left(-\frac{8}{3}\right) = \frac{4 \times (-8)}{5 \times 3} = \frac{-32}{15} \][/tex]
Step 3: Write the quadratic equation using the sum and product of the roots.
In general, the quadratic equation based on the sum and product of the roots is given by:
[tex]\[ x^2 - (\text{sum of roots})x + (\text{product of roots}) = 0 \][/tex]
Plugging in our values:
[tex]\[ x^2 - \left(\frac{-28}{15}\right)x + \left(\frac{-32}{15}\right) = 0 \][/tex]
Simplifying the signs:
[tex]\[ x^2 + \frac{28}{15}x - \frac{32}{15} = 0 \][/tex]
Thus, the quadratic equation whose roots are [tex]\(\frac{4}{5}\)[/tex] and [tex]\(-2\frac{2}{3}\)[/tex] is:
[tex]\[ x^2 + \frac{28}{15}x - \frac{32}{15} = 0 \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.